BUDDHIST CAUSALITY AND THE FORTUNE-TELLING PRACTICES IN URBAN CHINA: A MIXED-METHODS STUDY OF KARMA–VIPĀKA INTEGRATION IN DIVINATORY DISCOURSE - Guangliang HOU; Chompoo Gotiram (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This article examines how Mahāyāna Buddhist causality—specifically, the triadic concepts of karma, vipāka, and pratītyasamutpāda—is operationalized within the symbolic and discursive systems of contemporary Chinese fortune-telling. Drawing on textual analysis, semi-structured interviews with fifteen diviners, a quantitative survey of 278 clients, and longitudinal case studies, this study proposes a five-layer